PENGARUH MOTIVASI BELAJAR TERHADAP HASIL BELAJAR MATA PELAJARAN PEMBUATAN POLA PADA SISWA DI SEKOLAH MENENGAH KEJURUAN TAHUN PELAJARAN 2022/2023: Motivasi belajar, Hasil belajar, Pembuatan pola - Nisa Pratiwi; Rizky Ridhani (Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to determine (1) learning motivation of class X students in fashion making in the subject of pattern making, (2) the learning outcomes of class X students in fashion in the subject of pattern making, (3) the influence of learning motivation on student learning outcomes of class X fashion at SMK Negeri 2 Godean. This research is a quantitative research with a correlational approach. The population in this study were all 106 students in class X Fashion Design at SMK Negeri 2 Godean with a sample of 51 students. Data collection using questionnaires and documentation. The research results show that (1)Student motivation is in the high category with a relative frequency of 49.01%,(2) Studentlearning results in the high category with a relative frequency of 43.13%, (3) there is an influence between learning motivation on student learning outcomes in class X dress code for the pattern subject with an rcount of 0.760 > rtable of 0.276. The coefficient of determinant R2 = 0.577, meaning that the influence exerted by learning motivation on learning outcomes is 57.7%.